Lessons learned and strategies used while teaching core-curriculum science courses to english language learners at a middle eastern university - Copeland Solas, Eddia; Wılson, Kenesha (Journal of Turkish Science Education, 2015)
This article describes a reflection on teaching strategies used and lessons learned by two western, expatriate university professors teaching core-curriculum science courses at a middle eastern university, where the native language is Arabic and the language of instruction is English. Descriptions of effective strategies used and the benefits and limitations of each are provided. No rigorous quantitative data were collected on the efficacy of the interventions. However, the authors did note a marked increase in student engagement and active learning, critical thinking, student self-confidence, science self-efficacy and student performance over five semesters. As more of the pedagogical techniques were employed instructors noticed an improvement in instructor evaluation scores and an increase in positive student comments.